PENGARUH STRATEGI KWL BERBANTU SOROGAN TERHADAP KETERAMPILAH MAHARAH QIRA'AH SANTRI USIA DINI - Siti Nur Khasanah; Nurrokhmatulloh; Hasan Syaiful Rizal; Amirul Mukminin (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2024)
This study aims to investigate the impact of applying the Know-Want to Know-Learned (KWL) strategy combined with the sorogan method on the reading skills (maharah qira’ah) of students at Madrasah Diniyah Asrama P Pondok Pesantren Ngalah. The background of this research is the suboptimal improvement in students' maharah qira’ah abilities through the teaching methods previously implemented. Therefore, the Know-Want to Know-Learned (KWL) strategy combined with sorogan was applied, where students were asked to state and write information they knew before, during, and after reading, while the teacher acted as a facilitator. This research uses a quantitative approach with a quasi-experimental method and a One-Group Pretest-Posttest Design. The subjects of this study were 22 third-grade students of Madrasah Diniyah Asrama P. The results showed a significant effect of using the KWL (Know-Want to Know-Learned) worksheets combined with sorogan in improving students' maharah qira’ah skills. This was evidenced by the results of a paired sample t-test, which showed a significance of <0.001, less than 0.05, indicating a significant difference and a positive effect from the implementation of the KWL (Know-Want to Know-Learned) strategy assisted by sorogan on students' maharah qira’ah skills.